Sex differences in pulmonary vascular control: focus on the nitric oxide pathway. Issue 11 (8th June 2017) - de Wijs‐Meijler, Daphne P. M.; Danser, A. H. Jan; Reiss, Irwin K. M.; Duncker, Dirk J.; Merkus, Daphne
Abstract: Although the incidence of pulmonary hypertension is higher in females, the severity and prognosis of pulmonary vascular disease in both neonates and adults have been shown to be worse in male subjects. Studies of sex differences in pulmonary hypertension have mainly focused on the role of sex hormones. However, the contribution of sex differences in terms of vascular signaling pathways regulating pulmonary vascular function remains incompletely understood. Consequently, we investigated pulmonary vascular function of male and female swine in vivo, both at rest and during exercise, and in isolated small pulmonary arteries in vitro, with a particular focus on the NO‐cGMP‐PDE5 pathway. Pulmonary hemodynamics at rest and during exercise were virtually identical in male and female swine. Moreover, NO synthase inhibition resulted in a similar degree of pulmonary vasoconstriction in male and female swine. However, NO synthase inhibition blunted bradykinin‐induced vasodilation in pulmonary small arteries to a greater extent in male than in female swine. PDE5 inhibition resulted in a similar degree of vasodilation in male and female swine at rest, while during exercise there was a trend towards a larger effect in male swine. In small pulmonary arteries, PDE5 inhibition failed to augment bradykinin‐induced vasodilation in either sex. Finally, in the presence of NO synthase inhibition, the pulmonary vasodilator effect of PDE5 inhibition was significantly larger in female swine both in vivo and in vitro. In conclusion, the present study demonstrated significant sex differences in the regulation of pulmonary vascular tone, which may contribute to understanding sex differences in incidence, treatment response, and prognosis of pulmonary vascular disease. Abstract : Both in isolated pulmonary small arteries and in vivo in exercising swine, there are inherent sex differences in the nitric oxide pathway in the pulmonary vasculature. These differences may contribute to sex differences observed in prevalence and severity, as well as treatment response to phosphodiesterase‐5 inhibition in pulmonary hypertension.